2020
DOI: 10.1038/s41598-020-69062-3
|View full text |Cite
|
Sign up to set email alerts
|

An end to the controversy over the microscopic detection and effects of pristine microplastics in fish organs

Abstract: The aquatic environment and the associated fish assemblages are being exposed to an increasing amount of microplastics. Despite the high number of publications on the presence of microplastics in fish, little is known about their uptake, translocation and accumulation within fish organs. Experimental studies on the detection and effects of pristine microplastics in fish have shown controversial and ambiguous results, respectively. Here, we conducted two experiments to detect and assess the impacts of dietary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 130 publications
(340 reference statements)
0
27
1
Order By: Relevance
“…The impacts of MP exposure have been extensively studied in aquatic animals (e.g. Barboza et al., 2018; De Sales‐Ribeiro et al., 2020; Karami et al., 2016; Romano et al, 2020), and sometimes with contrasting findings. This could be due to differences in MP type and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of MP exposure have been extensively studied in aquatic animals (e.g. Barboza et al., 2018; De Sales‐Ribeiro et al., 2020; Karami et al., 2016; Romano et al, 2020), and sometimes with contrasting findings. This could be due to differences in MP type and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Virgin microplastics are not causing imminent harm to fish after dietary exposure in S. aurata [150] and O. mykiss [28], and did not present evident tissue damage in Barbodes gonionotus exposed to PVC fragments (0.2, 0.5 and 1.0 mg/L) for 96 h [159]. Little is known about their uptake, translocation, and accumulation within fish organs [23]. MP/NPs showed that oxidative stress and its responding pathways, including inflammatory responses, could play the role of key events [132].…”
Section: Toxicity Of Microplastics and Nanoplastics In Digestive Tract: Intestinal Retention Time Uptake And Eliminationmentioning
confidence: 93%
“…Based on the histological analysis, significant changes in the MPs-treated gut tissues were observed: epithelial and villi damage has been described in zebrafish [154,171,172] as bowel wall thinning, cracking of villi, epithelial damage with splitting of enterocytes and increased volume of mucus [30,137]. In contrast, De Sales-Ribeiro et al [23] argue that the ingestion of microplastics does not induce any histopathological changes in zebrafish.…”
Section: Toxicity Of Microplastics and Nanoplastics In Digestive Tract Of Zebrafish: An Emerging Model To Study The Bioaccumulation And Tmentioning
confidence: 99%
See 2 more Smart Citations